Dietary soy, pork and chicken proteins induce distinct nitrogen metabolism in rat liver - Zixin Huang (Elsevier, 2021)
Diets have been shown to alter metabolism and gene expression. However, few data are available about changes in gene expression in liver after intake of different meat protein diets. This work aimed to explore the long-term effects of protein source on liver metabolic enzymes. Rats were fed protein diets for 90 days to study whether intake of chicken and pork protein diets promoted gene expression involved in hepatic metabolism. Liver proteome profiles were measured by iTRAQ labeling and LC–ESI–MS/MS. Chicken protein diet induced higher level of serum amino acids in rats than soy protein. Amino acid metabolizing enzymes were downregulated by pork and chicken protein diets compared with soy protein diet. Intake of meat protein diets downregulated enzymes involved in protein synthesis, disulfide bond formation, signal peptide addition, transport, localization, degradation and glycosylation modification, but upregulated enzymes involved in prolyl cis–trans isomerization for protein synthesis. Protein diets from different sources affected the amino acid supply, and further influenced ribosome assembly and protein synthesis through mTOR signaling pathway.